Chapter The languages of wine: negotiating intercultural exchanges through translation - Bertulessi, Chiara (Studi e saggi, 2021)
This paper discusses the cultural and linguistic mediation strategies involved in the compilation of a terminological tool aimed at facilitating the intercultural exchanges between Italy and China in the field of oenology, by taking the Dictionary of Italian wines and grape varieties (Italian - Chinese) (Bosc et al. 2019) as a case study. The main objectives of the dictionary compilation were the popularization of specialized wine language, the standardization of the names of Italian wines and grape varieties, and the translation of the Italian lexicographical definitions in Chinese. For this process to be effective in terms of intercultural communication and mediation, the negotiation of standardization and translation strategies needed to take into account the differences between the two cultures and languages involved as well as the constraints of the lexicographical genre. After delineating the historical background and presenting the purpose of the dictionary from the lexicographical perspective, the paper delves into the choices made in the compilation of the Chinese text.